2020
DOI: 10.3390/en13123058
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price and Energy Depletion Nexus in GCC Countries: Asymmetry Analyses

Abstract: Oil price has played a prominent role in oil exporter economies and may also affect energy depletion in oil-dependent countries. Considering asymmetry, the relationship between oil price (OP) and energy depletion has been investigated in the Gulf Cooperation Council (GCC) region from 1970 to 2017. We find asymmetrical positive effects of OP on the energy depletion in the panel of the GCC region. To avoid aggregation biasness in the panel estimates, we also conduct a time-series analysis on each GCC country. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Alkhateeb and Mahmood [35] Saudi Arabia A positive and asymmetrical relationship was found between oil prices and energy depletion.…”
Section: Mahmood and Zamil [27]mentioning
confidence: 99%
See 2 more Smart Citations
“…Alkhateeb and Mahmood [35] Saudi Arabia A positive and asymmetrical relationship was found between oil prices and energy depletion.…”
Section: Mahmood and Zamil [27]mentioning
confidence: 99%
“…In disaggregated analyses, they found that the construction sector and public sector played a great role in increasing remittances' outflows. Alkhateeb and Mahmood [35] probed the oil prices and energy depletion nexus and found that oil prices had a positive and asymmetrical effect on the energy depletion in the GCC region. Erdogan et al [32] probed the impact of oil price volatility on military expenditures in Bahrain, Kuwait, KSA, and Oman.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies tested the effect of oil price (OP) on different macroeconomic indicators. For instance, there are some studies on the effect of OP on energy depletion in GCC countries (Alkhateeb and Mahmood, 2020b), the effect of OP on stock markets of GCC countries (Siddiqui et al, 2019), the effect of OP on capital formation in GCC countries (Alkhateeb and Mahmood, 2021) the effect of OP on capital formation in GCC countries (Alkhateeb and Mahmood, 2020a), the effect of OP on consumption in Saudi Arabia (Mahmood and Zamil, 2019), the effect of OP on investments in Saudi Arabia (Mahmood and Alkhateeb, 2018) and the effect of OP on employment in Saudi Arabia (Alkhateeb et al, 2017a(Alkhateeb et al, , 2017b. In the MENA region, Slimane et al (2010) has corroborated a procyclicality of fiscal policy in the whole MENA region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of OP on the other macroeconomic indicators has also been investigated in the GCC region. For example, GCC literature corroborated that OP has a positive effect on the military spending (Erdogan et al, 2020), a positive effect on the energy depletion (Alkhateeb and Mahmood, 2020) a positive effect on the capital formation (Alkhateeb and Mahmood, 2021), a positive effect on the remittances outflows (De et al, 2019), a positive effect on trade performance (Metwally, 1993) and a positive effect on the exchange rate (Al Rasasi, 2017).…”
Section: Introductionmentioning
confidence: 99%